JOURNALIST PROFESSIONALISM ON ‘THE POST’ MOVIE BASED ON THE PERSPECTIVE OF ELEMENTS OF JOURNALISM - Oktaviani, Rizqy Nedia; Yesicha, Chelsy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The Post is a historical-drama movie that tells story about journalism in USA in 1971. This movie got many positive response from the critics on big medias and succesfully depicted the confrontation between media and government which is based on true story. The Post are made as the critic for Donald Trump’s administration and showing the point of view of the press which is oppressed, that is why the journalists on this movie is depicted as professionals. The purpose of this research is to analyze how is journalist’s professionalism from elements of journalism represented in The Post. This research used qualitative descriptive methods using Teun A. Van Dijk discourse analysis which is known as Social Cognition Theory, with element of analysis on text level which include micro strucutre, macro structure, and supertructure. Van Dijk’s discourse analysis mainly focused on the text, which is suitable with The Post that represented the journalist professionalism by the dialogue in it. The subject on this research are 11 scenes from The Post movie, object on this research are dialogues in The Post movie. Data gathering technique used on this research are observation and documentation. Data checking are done by triangulation and using references to support this research. This research shows that The Post represented the journalist who have high professionalism. It is delivered through the characters that hold the value of professionalism, which in this research are viewed based on the perspective of elements of journalism. There are 8 elements out of 10 elements of journalism that is represented on The Post; journalism first obligation is to the truth, its first loyalty is to citizens, it essence is a discipline of verification, its practitioners must maintain an independence from those they cover, it must serve as an independent monitor of power, it must strive to make the significant insteresting and relevant, it must keep the news comprehensive and in proportion, its practitioners have an obligation to exercise their personal conscience. Aside from that, there are also 2 elements of journalism that are not represented on the movie; journalism must provide a forum for public criticism and compromise, and citizens, too, have rights and responsibilities when it comes to the news. Key Word : Movie, The Post, Discourse Analysis, Journalism, Teun A. Van Dijk, Journalist Professionalism